POLICY OUTCOME ANALYSIS OF THE GUYUB RUKUN WASTE BANK POLICY PROGRAM BASED ON PERFORMANCE OF MANAGERS AND CUSTOMERS IN KEMIJEN VILLAGE SEMARANG - Fadhilla, Arlintyo Fitra; Rahman, Amni Zarkasyi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Abstract Semarang City as a Metropolitan City is often dealing with garbage. The total amount of daily waste generated in Semarang City comes from households, offices, traditional markets, commercial centers, public facilities, areas, and others. Seeing this, the government is aggressively managing waste, one of which is through the Garbage Bank. One of the waste banks in the city of Semarang is the Guyub Rukun Waste Bank. This study aims to further investigate the Policy Outcome of the Guyub Rukun Waste Bank Program in Kelurahan Kemijen, Semarang. The policy outcome is seen from the core outcome, intermediate outcome and long-term outcome. This research uses descriptive qualitative research methods with interview data collection techniques and participatory observation. The results obtained from this study indicate that in terms of Initial Outcome the results obtained are reduced waste so that the environment is clean as well as an increase in the capacity of the community. Then from the perspective of Intermediate Outcome, it can be seen that the mindset of society towards waste has begun to change and the reach of customers from Guyub Rukun Waste Bank is expanding. The results of the long-term outcome itself can be seen from the increase in the community's economy from the results of waste collection and the establishment of cooperation with other parties in the sustainability and development of the Waste Bank, although in terms of the amount of pollution it has not been able to show significant results. Suggestions that can be given are: There needs to be reciprocal innovation, regular waste volume data collection, new activities, and regular monitoring.